STUDENTS’ PERCEPTIONS OF AI GRAMMAR TOOLS IN ENGLISH LEARNING: A SYSTEMATIC REVIEW - phalaguna, ida bagus gde (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2025)
This systematic review investigates students’ perceptions of AI grammar correction tools in English language learning across diverse educational contexts. Analyzing 32 studies, the findings reveal that 78.1% of students globally hold positive perceptions, appreciating tools like Grammarly, ChatGPT, and Quillbot for improving grammar accuracy, vocabulary, and writing efficiency. However, 18.75% of studies report mixed perceptions, highlighting concerns about over-reliance, inaccuracies, and ethical issues, while 3.13% express negative views, emphasizing dependency risks and limited contextual understanding. The review underscores the dominance of Grammarly and ChatGPT in language learning, with regional variations in adoption and challenges. Pedagogical implications suggest integrating AI tools with human oversight to enhance learning outcomes while addressing ethical and dependency concerns. The study calls for further research on the long-term impacts and comparative effectiveness of AI versus traditional feedback methods.